The economic aspects of chilli production in Central Java - Madhusudan Bhattarai; Joko Mariyono (Economic Journal of Emerging Markets, 2016)
This study analyses the economic aspects of chilli in Central Java where chilli is massively and intensively cultivated. Data for this study is compiled during 2009-2011 in three chilli producing districts: Brebes, Magelang and Rembang. Analyses is conducted using qualitative and quantitative approaches. The results indicate that many important findings related to economic aspects of chilli. There are various ranges of economic aspects across regions. The main findings is that chilli provided positive net returns, has relatively high economic risk and intensive use of chemicals. The policies related to improvement of chilli cultivation need to be formulated based on local specific constraints.